2015
DOI: 10.1158/0008-5472.can-15-0684
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Exerts Antimetastatic Effects by Dissociating Clusters of Circulating Tumor Cells

Abstract: Clusters of circulating tumor cells (CTC) exhibit more robust metastatic properties than single CTC. Thus, understanding the distinct behaviors of CTC clusters and how CTC clustering is regulated may offer new insights into how to limit metastasis. In this study, we utilized an in vivo confocal system to observe the clustering behavior of CTC in real time, finding that the number of clusters increased proportionally with the growth of the primary tumor. Our experiments also indicated that the flow rate of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 40 publications
3
41
0
Order By: Relevance
“…Recently, a Korean group succeeded in prolonging survival in a mouse model of breast cancer by dissociating CTC clusters using urokinase (82), making a first step in CTC cluster-relevant treatment. However, because the dissociated CTCs can still form metastases, the effects of such strategy may be mild and needs further evaluation.…”
Section: Clinical Application Of Ctc Clustersmentioning
confidence: 99%
“…Recently, a Korean group succeeded in prolonging survival in a mouse model of breast cancer by dissociating CTC clusters using urokinase (82), making a first step in CTC cluster-relevant treatment. However, because the dissociated CTCs can still form metastases, the effects of such strategy may be mild and needs further evaluation.…”
Section: Clinical Application Of Ctc Clustersmentioning
confidence: 99%
“…, Claudine Soria 2, † , Marc Pocard 1 , Massoud Mirshahi 1,2 , and Jeannette Soria 1,2 We were surprised by the results of Choi and colleagues showing that urokinase exerts antimetastatic effects by dissociating clusters of circulating tumor cells (1).…”
mentioning
confidence: 99%
“…We appreciate two commentaries from Dr. Alonso and Dr. Soria’s groups regarding our recent publication on ‘highly metastatic property of clustered circulating tumor cells(CTCs)’ In our research, we suggested the breakdown of CTC cluster slows metastasis pace with preclinical experiments; urokinase plasminogen activator (uPA) utilized to dissociate the CTC cluster showed no effect on primary tumor growth, but the number of metastasized nodules was reduced, expanding survival rate of the animals (1). …”
mentioning
confidence: 99%